ANGI-03. PHARMACOLOGICAL TARGETING OF APELIN/APLNR SIGNALING BLUNTS THERAPY RESISTANCE TO VEGFA/VEGFR2 ANTI-ANGIOGENIC TREATMENT IN GLIOBLASTOMA. (11th November 2019) - Kälin, Roland; Mastrella, Giorgia; Hou, Mengzhuo; Li, Min; Stoecklein, Veit; Zdouc, Nina; Volmar, Marie; Miletic, Hrvoje; Reinhard, Sören; Herold-Mende, Christel; Kleber, Susanne; Eisenhut, Katharina; et al.
Abstract: Anti-angiogenic therapy of glioblastoma with bevacizumab, a vascular endothelial growth factor-A (VEGFA) blocking antibody, may accelerate tumor cell invasion and induce alternative angiogenic pathways. We investigated the roles of the pro-angiogenic receptor APLNR and its cognate ligand apelin in VEGFA/VEGFR2 anti-angiogenic therapy against distinct subtypes of glioblastoma. In proneural glioblastoma, apelin levels were downregulated by VEGFA or VEGFR2 blockade by use of bevacizumab or ramucirumab, respectively. A central role for apelin/APLNR in controlling glioblastoma vascularization was corroborated in a serial implantation model of the angiogenic switch that occurs in human glioblastoma. Apelin and APLNR are broadly expressed in human glioblastoma, and knockdown or knockout of APLN in orthotopic models of proneural or classical glioblastoma subtypes massively reduced glioblastoma vascularization as compared with controls. What is more, direct infusion of the bioactive peptide apelin-13 was able to rescue this vascular loss-of-function phenotype, demonstrating the specific control of tumor vascularization by apelin/APLNR signaling. While high levels of apelin correlated with reduced tumor cell invasiveness, the reduction in apelin expression led to accelerated glioblastoma cell invasion. Analysis of stereotactic glioblastoma biopsies from patients as well as from in vitro and in vivo experiments revealed increased dissemination of APLNR-positive tumor cells when apelin levels were reduced. Most interestingly, application of apelin-F13A, a mutant APLNR ligand, blocked both tumor angiogenesis and glioblastoma cell invasion. Furthermore, co-targeting VEGFR2 and APLNR synergistically improved survival of mice bearing proneural glioblastoma. In summary, we show that apelin/APLNR signaling controls glioblastoma angiogenesis and invasion directly, and that both pathological features are blunted by apelin-F13A. We suggest that apelin-F13A can improve the efficiency and reduce the side effects of established anti-angiogenic treatments for distinct glioblastoma subtypes.